THE EFFECT OF WORK SYSTEMS, ORGANIZATIONAL BEHAVIOR, PSYCHOLOGICAL WELL-BEING, AND ORGANIZATIONAL COMMITMENT, ON JOB SATISFACTION - Dewi, Truli Susatyo; Abadi, Ferryal (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
State Civil Apparatus (ASN) must have high performance. High-Performance Work Systems (HPWS) can increase employee and organizational productivity. In this study, we examine how HPWS relates to Organizational Citizenship Behavior (OCB), how psychological well-being (PWB) influences job satisfaction, and examine how PWB, organizational commitment, and job satisfaction function as mediators of HPWS-OCB interaction with the ASN population in 42 DKI Jakarta Provincial Government Organizations (OPD). Sampling was taken by purposive sampling, with ASN requirements with a minimum working period of 1 year. The survey was conducted in June 2023 to obtain data from 185 respondents who received 33 questions via Whatsapp. The data were evaluated using the Structural Equation Model Partial Least Square (SEM-PLS). HPWS has a significant positive effect on PWB and organizational commitment. HPWS does not affect OCB. The positive HPWS-OCB relationship can be fully moderated by PWB. PWB has a significant positive effect on organizational commitment and will increase OCB. HPWS does not affect job satisfaction. HPWS through PWB mediation and organizational commitment has a significant effect on job satisfaction. Organizational commitment does not mediate the HPWS-OCB relationship. Job satisfaction does not affect OCB. Government organizations should implement HPWS in ASN management so that ASN feels PWB and in the end voluntarily carry out OCB, which leads to improving the quality of excellent service and organizational performance